Character Education Values of Radin Inten II’s Against The Dutch Colonization For Learning Local History - Wahyu Dwi Anggraeni; Aman Aman; Johan Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to explore the values of character education in the resistance of Radin Inten II against the Dutch colonization. The method used is the historical method with heuristic steps, criticism, interpretation, and historiography. The data collection techniques used is library research. The results of the research are described briefly related to the biography and resistance of Radin Inten II as a local figure who fought against the Dutch colonization. The values of character education contained in this material are hard work, love for the country, a national spirit, communicative competence, and responsibility. These character values can be actualized by teachers to students in a local history learning process that is integrated with Indonesian history subject matter in high schools. It is expected that students can emulate the figure of a local figure named Radin Inten II, especially for those who live in Lampung area.